2012
DOI: 10.1186/1742-2094-9-280
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Kir4.1 expression in astrocytes and astrocytic tumors: a role for interleukin-1 β

Abstract: ObjectiveDecreased expression of inwardly rectifying potassium (Kir) channels in astrocytes and glioma cells may contribute to impaired K+ buffering and increased propensity for seizures. Here, we evaluated the potential effect of inflammatory molecules, such as interleukin-1β (IL-1β) on Kir4.1 mRNA and protein expression.MethodsWe investigated Kir4.1 (Kcnj10) and IL-1β mRNA expression in the temporal cortex in a rat model of temporal lobe epilepsy 24 h and 1 week after induction of status epilepticus (SE), us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 66 publications
4
51
0
Order By: Relevance
“…No changes in astrocytic Kir currents were found in a kainate model of epilepsy (Takahashi et al 2010). Recently, down-regulation of Kir4.1 mRNA and protein has been reported in the context of epilepsy and inflammation, possibly mediated by the proinflammatory cytokine interleukin (IL)-1β (Zurolo et al 2012), whereas another study reported enhanced Kir4.1 expression in a rat pilocarpine model (Nagao et al 2013). Unfortunately, functional consequences of these changes have not been assessed in the latter two studies.…”
Section: K+ Homeostasis Is Disturbed In Epilepsymentioning
confidence: 99%
“…No changes in astrocytic Kir currents were found in a kainate model of epilepsy (Takahashi et al 2010). Recently, down-regulation of Kir4.1 mRNA and protein has been reported in the context of epilepsy and inflammation, possibly mediated by the proinflammatory cytokine interleukin (IL)-1β (Zurolo et al 2012), whereas another study reported enhanced Kir4.1 expression in a rat pilocarpine model (Nagao et al 2013). Unfortunately, functional consequences of these changes have not been assessed in the latter two studies.…”
Section: K+ Homeostasis Is Disturbed In Epilepsymentioning
confidence: 99%
“…Furthermore, the low expression of several potassium channel genes observed in GG suggests a disturbed ion homeostasis and transport that could represent an additional potential mechanism leading to increased excitability in GNT [57]. Interestingly, evaluation of the inward-rectifying potassium channel on astrocytes Kir4.1 in tumor specimens showed a significantly lower Kir4.1 expression in the specimens of patients with epilepsy compared to patients without epilepsy [70]. Over the last decade, an increasing number of observations support the role of inflammation in the pathophysiology of human epilepsy (for reviews see [71][72][73][74] ; Fig.…”
Section: Epileptogenesismentioning
confidence: 99%
“…Accordingly, the activation of these pathways has been shown to play a pivotal role in seizure precipitation and recurrence using a post-translational mechanism independent of transcriptional activation nuclear factor kappa-B and involving the rapid activation of Src kinases and phosphorylation of the NMDA-NR2B receptors [177][178][179]. IL-1β may also regulate the expression of inward-rectifying potassium channels on astrocytes (such as Kir4.1), influencing the potassium buffering, which could represent an additional mechanism contributing to neuronal hyperexcitability and seizure development [70].…”
Section: Epileptogenesismentioning
confidence: 99%
“…Cultured astrocytes were shown to swell following Kir4.1 silencing with siRNA (Obara- Michlewska et al, 2011) and also when Kir4.1 expression decreased following oxygen and glucose deprivation (Benesova et al, 2012). Animal model studies have suggested that decreased Kir4.1 mRNA and/or protein content in the brain contributes to the pathogenesis of various CNS disorders, including epilepsy (Stewart et al, 2010;Zurolo et al, 2012), ischaemia (Pivonkova et al, 2010), amyotrophic lateral sclerosis (Bataveljić et al, 2012;Kaiser et al, 2006), congenital hyperammonaemia (Lichter-Konecki et al, 2008) and hepatic encephalopathy (HE) associated with acute toxic liver failure (ALF) (Obara- Michlewska et al, 2011). However, the mechanism underlying pathological loss of Kir4.1 channels is unknown.…”
Section: Introductionmentioning
confidence: 98%